Fault Avoidance Queue based Load Balancing Protocol (FAQ-LB) for Multipath Routing in Wireless Sensor Networks - N.V.Chinnasamy, Dr.A.Senthilkumar (International Journal of Advanced Science and Technology, 2020)
Wireless Sensor Networks are highly distributed framework of small light weighted wireless nodes installed in large numbers to observe the surroundings by measuring physical factors such as temperature, pressure, light, humidity, vibration, etc. Routing protocols are employed for communication. Routing protocols help in finding the most suitable path to pass on the data and support the routes in the network. A lot of routing protocols have been proposed in WSNs. But the use of these techniques is questionable when it comes to fault tolerance and security issues. Maintaining a secure fault tolerant reliable network is the need of the hour. In this paper, an overview of the various efficient multipath routing protocols have been studied and the merits of the best techniques are best combined to propose a hybrid protocol framework that is optimal overcoming the fault tolerance and security problems. Lastly, the possible open challenges and research directions are addressed for future inquiry.